Energy and comfort in spaces equipped with ascendant airflow - Conceição, Eusébio; Gomes, João; Conceição , M. Inês; Lúcio, M. Manuela; Awbi, Hazim (CLIMA 2022 conference, 2022)
This article presents a numerical study on an impinging jet ventilation system applied in a virtual office with the aim of improving indoor air quality (IAQ) and thermal comfort conditions for its occupants. The study was carried out for winter conditions, also evaluating the thermal energy consumption obtained in the acclimatized space by the proposed ventilation system. The numerical model used is based on the coupling of two numerical models, the Computational Fluid Dynamics to simulate the heat and mass turbulent flow, and the Human Thermal Modelling to evaluate the human and clothing thermal response. A third numerical model, the Building Thermal Modelling, was used to provide some input data required for the two aforementioned models. The evaluation of the thermal comfort is done by the Predicted Percentage of Dissatisfied (PPD) people index. The evaluation of the IAQ is done by the dioxide carbon (CO2) concentration in the breathing zone of occupants. The evaluation of the impinging jet ventilation system is done by the Air Distribution Index (ADI). This study was done in a virtual chamber occupied by four virtual manikins seated around a table. The impinging jet ventilation system has an inlet system based on four ducts located in the corners of the chamber, whose air terminal devices are 0.25 m from the floor, and an outlet system, whose air terminal device is located close to the ceiling central area. This numerical study considered different values of the airflow rate for the impinging jet ventilation system. When the airflow rate increases, the level of IAQ, the level of thermal comfort and the ADI improve. Moreover, results obtained for PPD and CO2 show values within acceptable limits accordingly to the international standards.